Key Sector Analysis by IO Networks: Evidence from Turkey - Cirpici, Yasemin Asu (SAVEZ EKONOMISTA VOJVODINE, 2024)
In this study, the key sectors of Turkey are determined using InputOutput (IO) network analysis. Different centrality measures are analyzed and compared. Accordingly, eigenvector, page rank, hub, and authority centralities are calculated. The effects of an economic shock are also analyzed using random walk centrality and counting betweenness. Findings indicate that the key sectors are Wholesale and Retail Trade; Repair of Motor Vehicles, Transport, Storage and Communications, Agriculture, Hunting and Forestry, Construction, Real Estate Activities, and Textiles, Textile Products, Leather and Footwear. Furthermore, the same sectors are determined to be vulnerable to economic shocks.
Keywords: Input-output networks; Key sector; Centralities; DEPENDENCY; PAGERANK; ECONOMY; Business & Economics